NaCl Inhibits Citrinin and Stimulates Monascus Pigments and Monacolin K Production - Zhen, Zhixin; Xiong, Xiaoqian; Liu, Yingbao; Zhang, Jialan; Wang, Shaojin; Li, Li; Gao, Mengxiang (Toxins, 2019)
Applications of beneficial secondary metabolites produced by Monascus purpureus (M. purpureus) could be greatly limited for citrinin, a kidney toxin. The link of NaCl with cell growth and secondary metabolites in M. purpureus was analyzed with supplementations of different concentrations of NaCl in medium. The content of citrinin was reduced by 48.0% but the yellow, orange, red pigments and monacolin K productions were enhanced by 1.7, 1.4, 1.4 and 1.4 times, respectively, compared with those in the control using NaCl at 0.02 M at the 10th day of cultivation. NaCl didn’t affect the cell growth of M. purpureus. It was verified through the transcriptional down-regulation of citrinin synthesis genes (pksCT and ctnA) and up-regulation of the Monascus pigments (MPs) synthesis genes (pksPT and pigR). Moreover, the reactive oxygen species (ROS) levels were promoted by NaCl at the 2nd day of cultivation, and then inhibited remarkably with the extension of fermentation time. Meanwhile, the activities of superoxide dismutase (SOD) and catalase (CAT), and the contents of total glutathione (T-GSH) were significantly enhanced in the middle and late stages of cultivation. The inhibition effect on colony size and the growth of aerial mycelia was more obvious with an increased NaCl concentration. Acid and alkaline phosphatase (ACP and AKP) activities dramatically increased in NaCl treatments. NaCl could participate in secondary metabolites synthesis and cell growth in M. purpureus.